ONLINE ASSESSMENT IN THE LIGHT OF COVID-19-IMPOSED CHANGES IN HIGHER EDUCATION IN SERBIA (Živi jezici: Journal for Foreign Languages and Literatures, 2021)
In this article, we present a qualitative analysis of online learning environments set up in response to the pandemic-induced lock down in higher education institutions in Serbia. The focus is on competence-based assessment approaches and the possibility of their implementation in higher education in Serbia. Through interviews with six teachers, we aim to outline some characteristics of higher education online courses and platforms used. Furthermore, we discuss the means of extending these approaches as to include online assessment. We also analyse prerequisites and issues in online assessment in the examined context. We argue that assessment in higher education is in a need of a profound change and could greatly benefit from the implementation of peer and self-assessment.
Keywords: online assessment; blended learning; higher education; technology in education; peer assessment; self assessment